ANALYSIS OF INVESTOR BEHAVIOR IN THE ISLAMIC CAPITAL MARKET WITH AN APPROACH TRA (THEORY OF REASONED ACTION) - Istu Putri Swasti (Universitas muhammadiyah malang, 2020)
The development of the capital market in Indonesia is very significant, with the implementation of the Yuk Savings Stock campaign to increase the number of domestic investors in Indonesia. The Indonesian Central Securities Depository (KSEI) noted that as of August 9, 2019, the number of capital market investors reached 2,070,394 people, an increase of 27.8 percent from the position in December 2018. This study aimed to find out and analyze Investment Knowledge on Attitudes, Investment Motivation on Attitudes, Perceptions of Risks towards Attitudes, Attitudes Influence Interests, Subjective Norms Affect Investment Interests, and Investment Interests Affect Investors Behavior in Sharia Capital MarketsThe population in this study are Islamic Capital Market investors in the DIY & Central Java region. Samples taken in this study are some Shariah Investors in DIY & Central Java, which total 213 respondents. Sampling using non-probability techniques with convenience sampling method and research models will be analyzed using Structural Equation Model (SEM), using the help of AMOS software.The results of this study indicate that investment knowledge has a significant negative effect on attitude, investment motivation has a significant positive effect on attitude, perception of risk has a significant negative effect on attitude, attitude has a significant positive effect on interest, subjective norms has a significant positive effect on interest and interest has a significant positive effect on investor behavior.Keywords: Investment Knowledge, Investment Motivation, Risk Perception, Attitude, Subjective Norms, Investment Interest, Investor Behavior